Role-Playing Learning Method in Shaping Commendable Morals of Students in Islamic Education Subjects - Huda, Ali Anhar Syi’bul; Syahidin, Syahidin; Nurhuda, Abid (Utan Kayu Publishing, 2023)
This study aims to determine the implementation of the role-playing learning method in PAI subjects in forming students' commendable morals. The research was conducted using a qualitative approach with the literature study method, collecting data through the latest and old literature (journals, books, proceedings) as primary data and sources from the internet as secondary data, the results of which were then described descriptively. The results obtained show that the role-playing learning model helps and is effective in developing students' commendable characteristics such as honesty, discipline, and good manners toward learning. This can happen because students gain direct experience by playing one character or another. What they experienced internalized within themselves so that there was a good change from before. Then based on the literature review it was also found that the role-playing learning method could be implemented in PAI subjects with the teaching material of the Story of the Prophet Abraham. Through the story of Prophet Ibrahim, students gain experience on how to respect their parents, act well, be honest, obey, and trust. The research carried out can contribute to the development of learning methods for parties involved in education, with a variety of learning methods applied that can provide meaningful learning by both teachers and students. Abstrak: Penelitian ini bertujuan untuk mengetahui implementasi dari metode pembelajaran role playing pada mata pelajaran PAI dalam membentuk akhlak terpuji siswa. Penelitian dilakukan menggunakan pendekatan kualitatif dengan metode studi pustaka, pengumpulan data melalui literatur-literatur terbaru dan lama (jurnal, buku, prosiding) sebagai data primer dan sumber dari internet sebagai data sekunder yang kemudian hasilnya dijabarkan secara desriptif. Hasil yang didapatkan bahwa model pembelajaran role playing membantu dan efektif dalam menumbuhkembangkan karakter terpuji siswa seperti kejujuran, kedisplinan, dan adab yang baik terhadap berguru. Hal demikian dapat terjadi karena siswa mendapatkan pengalamannya secara langsung dengan memerankan satu tokoh atau peran lainnya. Dari apa yang mereka alami menginternalisasi dalam diri sehingga adanya perubahan yang baik dari sebelumnya. Kemudian berdasarkan telaah literatur juga didapati bahwa metode pembelajaran role playing dapat dilaksanakan pada mata pelajaran PAI dengan materi ajar Kisah Nabi Ibrahim. Melalui kisah nabi Ibrahim siswa mendapatkan pengalaman bagaimana cara menghormati orangtua, berlaku baik, jujur, taat, dan tawakal. Penelitian yang dilakukan dapat menjadi sumbangsih bagi pengembangan metode pembelajaran bagi pihak-pihak yang terlibat dalam dunia pendidikan, dengan adanya variasi metode belajar yang diterapkan mampu memberikan kebermaknaan belajar baik oleh guru maupun siswa.